PARTICLE SORTING MODULE WITH ALIGNMENT WINDOW, SYSTEMS AND METHODS OF USE THEREOF - LANKILA, Henry; DEMBSKI, Kyle (2022)
Aspects of the present disclosure include a particle sorting module having an opening that is configured for visualizing droplets of a deflected flow stream. Particle sorting modules according to certain embodiments include a housing having a proximal end, a distal end and a wall therebetween having an opening positioned in the wall that is configured for aligning the flow stream with one or more sample containers at the distal end. Systems and methods for aligning a flow stream with one or more sample containers and sorting particles of a sample (e.g., a biological sample) are also provided. Kits having one or more of the particle sorting modules suitable for coupling with a particle sorting system and for practicing the subject methods are also described.